Trivialization and Public Opinion : Slogans, Substance, and Styles of Thought in the Age of Complexity /: Slogans, Substance, and Styles of Thought in the Age of Complexity. ([2019]) - Bubak, Oldrich; Jacek, Henry J
No abstract available